Pengaruh Perbedaan Dosis Probiotik Boster pada Pakan Buatan terhadap Pertumbuhan Berat Mutlak Ikan Lele (Clarias sp.) Umur 1 Bulan–2 Bulan - Made Saha Apta Raditya; Didik Budiyanto; Sumaryam Sumaryam (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Giving probiotics such as probiotic boster on feed greatly helps the growth of absolute weight in Catfish seeds because the good bacteria contained in these probiotics help facilitate catfish seeds in digesting the feed so as to increase the efficiency of the feed. This study aims to see how effective the probiotic administration is. The study was conducted in Kramas District, Gianyar regency, Bali Province for 30 days using experimental methods, using a complete randomized design with a total of 4 treatments and 6 repetitions. Treatment A is by giving 3 ml of probiotic boster every 1 kg of feed. Treatment B by giving 5 ml probiotic boster every 1 kg of feed. Treatment C by giving 7 ml probiotic boster every 1 kg of feed. Treatment D by giving 9 ml probiotic boster every 1 kg of feed. In this study showed significantly different results on the addition of probiotic boster with different doses on the growth of absolute weight of catfish fry aged 1 month-2 months. Treatment D gave the highest result with an absolute weight gain of 55.33 grams, and treatment a showed the lowest result with an absolute weight gain of 25.17 grams. Water quality Data during the study obtained water temperature ranges from 27-29 oC, acidity ranges from 7-8, and dissolved oxygen ranges from 3.34 to 4.26 ppm. The results of the analysis of variance (ANOVA) of the three parameters of water quality there is no difference between the treatment and the life range of catfish fry (Clarias sp.)